Peran Pengasuhan Terhadap Penyesuaian Sosial Santri Baru di Pondok Pesantren Al Mubarok - Siti Mutmainnah; Tri Windi Oktara (Indonesian Journal of Educational Counseling, 2026)
This research aims to (1) determine the role of caregivers in the social adjustment of new students at the Al-Mubarok Islamic Boarding School in Serang City, (2) identify the challenges faced by caregivers in guiding new students through their social adjustment, and (3) understand the strategies used by caregivers in guiding new students through their social adjustment. The research method employs a qualitative approach with a case study design. Data collection techniques include interviews, observation, and documentation. Data analysis uses the Miles and Huberman theory, which involves data reduction, data display, and conclusion drawing. The findings indicate that caregivers play a crucial role in the social adjustment of new students at the Al-Mubarok Islamic Boarding School. This role is implemented through five aspects: spiritual (habituation of worship), intellectual (learning), physical (health activities), social (group interaction), and emotional (psychological support). The challenges faced by caregivers in implementing these aspects of social adjustment for new students lie in the diverse backgrounds of the students. The strategies employed during the social adjustment of new students include building mutual commitment and organizing daily collective activities while the students reside in the Islamic boarding school.